Canada and Great Power Competition
XXV, 363 p. 9 illus., 5 illus. in color.
Keywords: This book examines Canada Among Nations over the last year and projects forward into the year 2022. 2021 was a year of challenges for Canada and a watershed in its engagement with the global political economy. Beset by a pandemic, hemmed-in by an America-first administration in Washington and punitive recrimination from a Chinese government with global ambitions, the shrinking horizons of a foreign economic policy premised on liberal internationalism and multilateral institutionalism have sapped Canada’s global ambitions. David Carment is Professor of International Affairs at the Norman Paterson School of International Affairs, Carleton University, Canada. Laura Macdonald is Professor in the Department of Political Science and the Institute of Political Economy at Carleton University, Canada. Jeremy Paltiel is Professor of political science at Carleton University in Ottawa, Canada.